Nanopartículas magnetofluorescentes de SPION@SiO2 funcionalizadas com sondas ESIPT - Selli, Gisele Inês (2018)
In the present study, we investigated the synthesis and characterization of core-shell magnetofluorescent nanoparticles composed of an iron oxide core and silica shells functionalized with fluorophores, which emit by the ESIPT mechanism. The synthesis of the iron oxide nanoparticles was performed by the polyol method and the coating, using the Stober sol-gel synthetic route. The fluorophores 2- [5'-N- (3-triethoxysilyl) propylurea-2'-hydroxyphenyl] benzothiazole (HBT) and 2- [5'-N- (3-triethoxysilyl) propylurea-2'-hydroxyphenyl] benzoxazole (HBO) were coupled to the coated nanoparticles using a reflux system with ethyl acetate as solvent. The resulting nanoparticles have an iron oxide core with diameters of ≈ 10 nm and a silicon oxide shell with thicknesses of ≈ 10 and 16 nm. The peak patterns of the cores obtained by XRD correspond to the inverse spinel structure of magnetite structure. The nanoparticles do not present residual magnetization and hysteresis, indicating a superparamagnetic behavior, regardless of the shell size. The solid state spectra of fluorescence emission confirm the coupling between fluorophores and SPION@SiO2, and the fluorescent properties of NPs. The samples showed Stokes displacements greater than 150 nm. The fluorescence emission spectra for the liquid dispersions, HBO and HBT fluorophores showed however, a behavior that depends on the presence of iron oxide nanoparticles, even in the presence of silica shell. Fluorescence suppression has been observed in most of the systems, however the mechanism by which suppression occurs is unclear the synthesized NP systems have both magnetic and fluorescent characteristics with potential to be used as contrast agents in biomedical imaging.